2006
DOI: 10.1080/13854040590947434
|View full text |Cite
|
Sign up to set email alerts
|

The Word Reading Test of Effort in Adult Learning Disability: A Simulation Study

Abstract: The Word Reading Test (WRT) was designed to detect effort problems specific to a learning disability sample. The WRT and the Word Memory Test (WMT) were administered to two simulator and normal control groups. The WRT showed excellent receiver operating characteristics (e.g., 90% sensitivity and 100% positive predictive power) and outperformed the WMT in detecting both reading and mental speed simulators. This finding and a double dissociation between reading and speed simulators on WRT errors and reaction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In cases of suspicious claims of specific cognitive impairment, such as dyslexia, standardized forced-choice testing is recommended and dedicated SVTs have been developed for this purpose, such as the Word Reading Test (WRT; Osmon, Plambeck, Klein, & Mano, 2006). The Emotional Numbing Test (MENT; Morel, 1998) is another example of a standardized forced-choice SVT.…”
Section: The Forced-choice Svt and Its Rationalementioning
confidence: 99%
“…In cases of suspicious claims of specific cognitive impairment, such as dyslexia, standardized forced-choice testing is recommended and dedicated SVTs have been developed for this purpose, such as the Word Reading Test (WRT; Osmon, Plambeck, Klein, & Mano, 2006). The Emotional Numbing Test (MENT; Morel, 1998) is another example of a standardized forced-choice SVT.…”
Section: The Forced-choice Svt and Its Rationalementioning
confidence: 99%
“…Students in the simulation condition were emailed to ask them to malinger dyslexia during testing and to prepare themselves for testing by gathering information about dyslexia. The study thus differs slightly from previous studies in which malingerers either had no preparation [ 8 ] or were presented with information and instructions on dyslexia and its symptoms [ 4 6 ]. Asking students to find their own information on dyslexia and decide on their strategies before testing more clearly reflects what actual malingerers might do before testing.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, about half of the malingerers performed extremely poorly on a word reading accuracy task. On this task, students with dyslexia did not differ from typical readers, indicating that this task might function as a performance validity test [ 4 , 5 , 7 , 8 ]. Poor performance on this particular task provides a contra-indication for dyslexia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emerging data show that test-takers motivated to underperform on exam adopt differing strategies (Boone, 2009;Larrabee, 2004;Nitch et al, 2006;Tan, Slick, Strauss, & Hultsch, 2002) with only 16% failing all measures of response bias administered (Boone, 2009). Osmon and colleagues (Osmon, Plambeck, Klein, & Mano, 2006) observed that simulators feigning reading impairment were better detected by a test specifically developed to identify feigned reading deficits than by a commonly used verbal memory effort indicator (Word Memory Test). Additional cases have been reported (Boone, 2009) showing that individuals feigning verbal memory impairment may not be detected by visual memory effort measures (e.g., TOMM, Rey 15-item), while individuals feigning visual perceptual/spatial/memory deficits are not necessarily captured by verbal memory effort indicators (e.g., Warrington Recognition Memory TestWords, Rey Word Recognition Test).…”
Section: Discussionmentioning
confidence: 99%